2013
DOI: 10.1179/1743290112y.0000000032
|View full text |Cite
|
Sign up to set email alerts
|

Design guidelines for PM parts subject to dry rolling–sliding wear

Abstract: This work improves the systematic approach proposed in previous papers, aimed at defining design criteria specific for powder metallurgy (PM) parts subject to wear in application. Dry rolling-sliding tests have been performed on PM steels obtained under different process conditions, and the results have been used as a knowledge base in the proposed design procedure to evaluate the effect of the material variables (porosity and microhardness) and geometrical parameters (contact length) on wear resistance. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In two previous works, the anisotropy of dimensional variations of different iron alloys was investigated by dilatometry, and the evidence of a significant shrinkage in alpha field below the Curie point was obtained. 2,3 Shrinkage kinetics in the 600–700°C temperature range was discussed with reference to the shrinkage model based on volume and grain boundary diffusion proposed by German, 1 and the diffusion coefficients calculated from experimental curves result much higher than those reported in literature for an equilibrium density of structural defects in the iron lattice. The hypothesis that diffusivity is strongly increased by dislocation introduced in the particle contact regions by prior cold compaction was then proposed to justify not only the enhanced shrinkage kinetics but even its anisotropy.…”
Section: Introductionmentioning
confidence: 97%
“…In two previous works, the anisotropy of dimensional variations of different iron alloys was investigated by dilatometry, and the evidence of a significant shrinkage in alpha field below the Curie point was obtained. 2,3 Shrinkage kinetics in the 600–700°C temperature range was discussed with reference to the shrinkage model based on volume and grain boundary diffusion proposed by German, 1 and the diffusion coefficients calculated from experimental curves result much higher than those reported in literature for an equilibrium density of structural defects in the iron lattice. The hypothesis that diffusivity is strongly increased by dislocation introduced in the particle contact regions by prior cold compaction was then proposed to justify not only the enhanced shrinkage kinetics but even its anisotropy.…”
Section: Introductionmentioning
confidence: 97%
“…Sonsino [4] found that the fatigue properties of PM components are inferior to those of wrought or cast parts. Cristofolin [5] focused on the effect of material variables (i.e., porosity and micro-hardness) and geometric parameters (i.e., contact length) on wear resistance in dry rolling-sliding contact. He built a knowledge base usable in the design step to take account of the effects of material variables (porosity and microhardness) and geometric parameters on wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The sintered density was measured by the water displacement method. The load bearing surface (Mr 2 ) was determined from the Abott–Firestone curves [8] recorded on the lateral surface of the rings. It resulted 0.79 and 0.83 for the low and high density specimens, respectively.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%